Fishery waste valorization: Sulfated ZrO2 as a heterogeneous catalyst for chitin and chitosan depolymerization - Pappalardo, Valeria; Remadi, Yassine; Cipolla, Laura; Scotti, Nicola; Ravasio, Nicoletta; Zaccheria, Federica (Frontiers in Chemistry, 2022)
Chitin and chitosan are abundant unique sources of biologically-fixed nitrogen, mainly derived from residues of the fishery productive chain. Their high potential as nitrogen-based highly added-value platform molecules is still largely unexploited and a catalytic way for their valorization would be strongly desirable within a biorefinery concept. Here we report our results obtained with a series of heterogenous catalysts in the depolymerization of chitosan and chitin to acetylglucosamine. Copper catalysts supported on SiO2, SiO2–Al2O3, SiO2-ZrO2, ZrO2 and the corresponding bare oxides/mixed oxides were tested, together with a sulfated zirconia system (ZrO2-SO3H) that revealed to be extremely selective towards glucosamine, both for chitosan and chitin, thus giving pretty high yields (44% and 21%, respectively), with respect to the values reported so far. The use of a heterogenous catalyst alone, without the need of any additives or the combination with a mineral acid, makes these results remarkable.